The Dimensions of Transformational Leadership and Its Organizational Effects in Public Universities in Saudi Arabia: A Systematic Review - Ghuzayyil Saad Alessa (Frontiers Media S.A., 2021)
Organizations are dynamic entities, such that they are constantly developing and changing. As such, these entities require leadership capable of managing transformations. Transformational leadership is an effective leadership model that focuses on adapting to existing environmental circumstances whether through internal information, human and monetary resources, or different external variables. This study aims to highlight the characteristics of transformational leadership and their effects on the public universities in Saudi particularly, this study enlightens the urgent need to test the behavioral intentions in the public universities in Saudi Arabia. To achieve this goal, many major databases were used. The period of the study was set from 2011 to 2020 as the topic of the study is the current transformational leadership within the public universities in Saudi Arabia. There was a total of 47,400,000 studies on transformational leadership on Google, however, only 22 studies were reviewed which were entirely conducted in Saudi Arabian Universities. The results demonstrated that in the public universities in Saudi, transformational leadership is practiced across four dimensions: ideal effect, inspirational motivation, intellectual stimulation, and individual consideration. The documentary research approach was used to review the most recent aspects of administrative literature on the theory of transformational leadership and its organizational outcomes. In addition, NVIVO 11 was used to make a thematic analysis of the linkages between transformational leadership and organizational outcomes: organizational commitment, knowledge management practices, morale, employee empowerment, level of job satisfaction, administrative creativity, organizational citizenship behavior, and the level of transformation toward quality and job enrichment. Therefore, behavioral tendencies such as organizational commitment, empowerment, job satisfaction, and knowledge management practices have been studied more interestingly and critically. Furthermore, these behavioral aspects need to be explored more in public universities in Saudi Arabia.